PERAN SISTEM INFORMASI MANAJEMEN DALAM MENGOPTIMALISASI OPERASIONAL DI BANK UMUM SYARIAH - Khairunnisa Khalida; Nayla Novita Syahfitri; Dian Faturrahman Siregar; Nurbaiti (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This Study Aims To Analyze The Role Of Management Information Systems (Mis) In Optimizing Operations At Islamic Commercial Banks. The Research Method Used Is A Qualitative Approach With Literature Study And Descriptive Analysis Of Various Literature Sources Related To The Application Of Information Systems In Islamic Banking. The Results Of The Study Indicate That The Implementation Of Mis Plays An Important Role In Improving The Efficiency, Effectiveness, And Productivity Of Bank Operations Through Data Integration, Ease Of Supervision, And Acceleration Of The Decision-Making Process. In Addition, Mis Also Supports The Application Of Sharia Principles In Bank Operations By Strengthening Transparency, Accountability, And Risk Control. Thus, The Sustainable Management And Development Of Mis Is A Strategic Factor In Improving The Competitiveness And Service Quality Of Islamic Commercial Banks In The Digital Era.